Tripartite declaration of principles concerning multinational enterprises and social policy. 3rd ed. (Geneva, 2011)
"In the 1960s and 1970s, the activities of multinational enterprises (MNEs) provoked intense discussions that resulted in efforts to draw up international instruments for regulating their conduct and defining the terms of their relations with host countries, mostly in the developing world. This includes labour-related and social policy issues were among those concerns to which the activities of MNEs gave rise.